The effects of orally administered meloxicam and injectable trace mineral supplementation on weight gain, morbidity and mortality in newly-received, high-risk stocker calves and on serum trace mineral status before and after injectable trace mineral application - Hartschuh, Hattie E. (Kansas State University, 2014)
Crossbred bull calves at high risk for morbidity (n = 190; BW = 159 ± 68 kg) were received at a commercial stocker operation to evaluate the effects of meloxicam administered at the time of castration on performance and health through d 30 post-arrival. Calves were assigned randomly to receive either a whey-powder placebo (CON), 0.5 mg/kg BW meloxicam (LOW), or 1.0 mg/kg BW meloxicam (HIGH) administered orally. Calves were vaccinated, knife-castrated, and received experimental treatments on d 0. Meloxicam had no effect on ADG (P ≥ 0.63), morbidity (P = 0.66), or mortality (P = 0.62). A second study was conducted using crossbred calves from the southeastern US and Mexico (n = 472; BW = 227 ± 45 kg) to evaluate effects of an injectable trace-mineral solution administered at time of arrival at a commercial stocker operation on animal performance, health, and serum concentrations of Cu, Mn, Se, and Zn on d 0 and d 45. Calves were assigned randomly to receive saline (CON; 1.0 mL/45 kg BW) or injectable trace mineral (ITM; 1.0 mL/45 kg BW) on d 0. Average daily gain from d 0 to d 42, overall ADG from d 0 to d 139, mortality, and morbidity were not different (P ≥ 0.31) between treatments. Calves originating from the Southeastern US had greater (P < 0.01) overall ADG from d 0 to 139. There were no source effects (P ≥ 0.21) on initial serum mineral concentrations for Mn or Zn; however, cattle originating in Mexico had lesser serum Cu (P < 0.01) and cattle originating in the Southeastern US tended to have lesser serum Se (P = 0.06). On d 45, there were no treatment differences (P ≥ 0.20) in serum concentrations of Cu, Mn, or Zn but cattle that received ITM tended (P = 0.09) to have elevated serum Se concentrations compared to those that received CON.
Keywords: Calves; Trace minerals; Meloxicam; Animal Sciences (0475)